Hubungan antara Harga Diri dan Kepercayaan Diri dengan Motivasi Berprestasi Siswa SMA - Yeniar Indriana; Muhammad Dzikron Fadhlurrohman (Jurnal Psikologi Perseptual)
The purpose of this study is to determine the relationship between self-esteem and self-confidence to achievement motivation and also to find out the effective contribution given by the independent variable to the dependent variable. The study population consists of high school students majoring in science in grade XI, aged between 17 and 19 years. Eleventh grade science students were chosen because they already had sufficient self-esteem and self-confidence and were considered to have better achievements. Cluster random sampling was employed to select a research sample of 140 students. The scaled used in this study includes a self-esteem scale, a self-confidence scale, and an achievement motivation scale. This study uses multiple regression analysis because it uses two independent variables and one dependent variable. The study found that self-esteem and self-confidence have a partial and simultaneous influence on achievement motivation variables. The variables of self-esteem and self-confidence made a significant contribution of 18.7% to the achievement motivation variable. The variable of self-esteem has a greater influence on the achievement motivation variable, at 13.5%, compared to the variable of self-confidence, which has an influence of 5.2%. This study shows that a student's self-esteem and self-confidence can impact their motivation to achieve.